1987
DOI: 10.1128/aac.31.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro antibacterial activities of two new oral cephalosporins, ceftetrame (Ro 19-5247) and cefetamet (Ro 15-8074)

Abstract: The in vitro activities of two new oral cephalosporins, ceftetrame and cefetamet (Ro 15-8074), were tested against 990 clinical bacterial isolates in comparison with that of cephalexin. Both compounds were more active than cephalexin against gram-negative bacteria, inhibiting most isolates of the family Enterobacteriaceae at concentrations of .4 ,Ig/mi, but were not active against Acinetobacter species, most Pseudomonas species, Campylobacter jejuni, and Flavobacterium meningosepticum. Ceftetrame was also mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…T-2525 (cefterame) is the biologically active product of the orally administered prodrug (T-2588). T-2525 is active against gram-negative bacteria and Streptococculs pneumoniae, but is less active than cefaclor against staphylococci (2,11,13). R-3746 is the biologically active product of CS-807.…”
mentioning
confidence: 99%
“…T-2525 (cefterame) is the biologically active product of the orally administered prodrug (T-2588). T-2525 is active against gram-negative bacteria and Streptococculs pneumoniae, but is less active than cefaclor against staphylococci (2,11,13). R-3746 is the biologically active product of CS-807.…”
mentioning
confidence: 99%
“…Cefetamet is active against a large number of gramnegative microorganisms; at least 22 different species have been shown to be susceptible (1,4,5). T. pallidum can now be added to this list.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the active metabolite cefetamet is especially effective against gram-negative microorganisms; it is also active against a few gram-positive organisms (1,4,5). In vivo, cefetamet has been successfully used to treat pyelonephritis in rats and septicemia in mice (1).…”
mentioning
confidence: 99%
“…Cefaclor is active against gram-positive and some gram-negative bacteria but is hydrolyzed by various f-lactamases (13). Cefixime and cefteram (T-2525) (2,12,14) have good activity against gram-negative bacteria and streptococci and are not hydrolyzed readily by various P-lactamases, but these compounds have relatively low activities against staphylococci (2,6,12,14).…”
mentioning
confidence: 99%
“…BMY-28232 and BMY-28271 (the acetoxyethyl ester of BMY-28232) were synthesized at the Tokyo Research Center of Bristol Myers Research Institute, Ltd., Tokyo, Japan.-The other antimicrobial agents used in this study were obtained from the indicated sources: cefixime, Fujisawa Pharmaceutical Co., Ltd., Osaka, Japan; cefteram (T-2525, Ro 19-5247) and cefteram pivoxil (T-2588) (2,12,14), Toyama Chemical Co., Ltd., Tokyo, Japan; cefaclor, Shionogi Pharmaceutical Co., Ltd., Osaka, Japan; benzylpenicillin, Meiji Seika Kaisha, Ltd., Tokyo, Japan; cephaloridine, Nihon Glaxo Co., Ltd., Tokyo, Japan; and methicillin, Banyu Pharmaceutical Co., Ltd., Tokyo, Japan. Organisms. The bacterial strains used in this study were recent clinical isolates from various hospitals in Japan.…”
mentioning
confidence: 99%